The treatment of phrasal verbs in bilingual learner dictionaries: implications on language learning / Rafidah Kamarudin and Rosamund Moon - Kamarudin, Rafidah; Moon, Rosamund (Universiti Teknologi MARA, Negeri Sembilan, 2018)
The purpose of this study is to investigate how reference materials (i.e. dictionaries) commonly prescribed to Malaysian school learners address and describe a very common and important linguistic feature - phrasal verbs. Two bilingual learner dictionaries frequently recommended for secondary school learners in Malaysia were examined. Analysis of common phrasal verbs like pick up, come out, and go out was carried out by examining entries in the dictionaries that discuss this linguistic feature. Descriptive analysis was conducted to examine how this particular language form is described by looking at the selection of phrasal verbs, as well as information provided with respect to phrasal verbs. Results of the analysis have revealed some interesting findings with regard to the selection and description of phrasal verbs in these dictionaries, which may have also contributed to learners' difficulties in understanding and learning the language form. The paper will be concluded by discussing some recommendations with respect to the inclusion and selection of phrasal verbs in language reference materials particularly dictionaries in Malaysian schools.